A new species of Rhadinella (Serpentes: Dipsadidae) from the dry forest of Motagua Valley, Guatemala - Ariano-Sánchez, Daniel; Campbell, Jonathan A. (Zootaxa, 2018)
We describe a new species of Rhadinella from the dry forest and thorn scrub of Valle del Motagua, Guatemala, a region and habitat where the congeners were previously unrecorded. This species is related to the group of Rhadinella that have dark dorsal coloration, which mostly or completely obscures a pattern of longitudinal striping characteristic of the majority of species of Rhadinella. The new species has dark gray, almost black, dorsal coloration with barely discernible slightly darker striping. Top of the head is mostly blackish with irregular auburn-orange markings on the internasals, prefrontals, frontal, parietals, loreals, postoculars, temporals, and two ultimate supralabials. Most conspicuous features are an orange-auburn Y-shaped marking along frontal-parietal and interparietal sutures, followed by an orange nuchal collar. The closest relative of the new species, based on morphological similarities, appears to be Rhadinella pilonaorum, which occurs in a relatively mesic habitat of pine-oak forest located about 90 km southwest from the type-locality of the new species.